Gauri Poojan coinciding with Ganesh Chaturthi - Mumbai Archive Project Team (Jio Institute, 2024)
In Maharashtra, Gauri Poojan coincides with Ganesh Chaturthi, when the Goddess Gauri visits homes a day or two before the Ganesha idol is installed. Goddess Gauri is considered the mother of Lord Ganesha, and they are worshipped simultaneously.